Antifungal activity of three local Malaysian honeys on selected pathogenic fungi of otomycosis ; an in vitro evaluation - Hamid, Zubaidah (2015)
Introduction Honey has been used as foods and medicinal products since ancient times. Its antibacterial properties has extensively documented. Contrarily, limited antifungal efficacy of honey was illustrated. Furthermore, in recent years, there are increasing in the antifungal drugs resistance. This drives the need to pursuit for natural solution which is more effective and safe. Honey, a natural solution attracted interest of its potential antifungal effect. They are various types of Malaysian honey. However, to date, no extensive studies on it antifungal properties have been conducted. Hence, this study evaluates antifungal effect of three Malaysian honeys against two most common pathogenic fungi of otomycosis. All honeys used in this study are unique. Tualang is a multifloral honey. Meanwhile Akasia are extraflorial honey and Kelulut are honey from stingless bee. Objectives To investigate the antifungal action of three types of Malaysia honeys (Akasia, Kelulut and Tualang) against Aspergillus niger and Candida albicans. This study also investigates honey with strongest antifungal effect. Methodology and study design This is a laboratory-controlled prospective study. Different concentrations of three types of Malaysian honey studied in vitro for their anti fungal activity on fungal isolates of Aspergillus niger and Candida albicans. Four different concentrations of SDA media incorporated with honey; 5 percent (w/v), 10 percent (w/v), 15 percent (w/v) and 25 percent (w/v) act as media. The numbers of colonies on SDA media alone were compared with SDA with honey. Statistical test of Paired t-Test and Wilcoxon Signed Ranks Test applied. Results In vitro, all three Malaysia honeys used, has significant antifungal effects on two most common pathogenic fungi of otomycosis. Tualang and Akasia have equal concentration for antifungal effect towards both fungi at 10 percent (w/v). Meanwhile Kelulut already demonstrate the effect at 5 percent (w/v). The antifungal efficacy is proportionate to concentration of all three honeys proceeding to total inhibition. Total inhibition noted to be equal for both Candida albicans and Aspergillus niger, for each individual honey except Akasia. Akasia need higher concentration for total inhibition of Aspergillus niger; 15 percent (w/v) compare to Candida albicans at 10 percent (w/v). For Kelulut it was at 10 percent (w/v) and Tualang at 25 percent (w/v). Among three honeys tested, Kelulut demonstrates the strongest antifungal effect towards both fungi. Conclusion This study demonstrates in vitro antifungal activity of three Malaysian honeys against two known pathogenic fungi of otomycosis. Hence, it has potentials as alternative agents in the treatment of otomycosis. Keywords : Madu Malaysia, Otomikosis, Aspergillus niger, Candida albicans, Tualang, Kelulut, Akasia